Structural characterization and preventive effect on non-alcoholic fatty liver disease of oligosaccharides from Bletilla striata. Issue 8 (7th April 2022) - Hu, Baifei; Yang, Huabing; Chen, Guangming; Sun, Xiongjie; Zou, Xiaojuan; Ma, Jun; Yao, Xiaowei; Liang, Qiong; Liu, Hongtao
Abstract : The structural characteristics of BOs were identified and their preventive effects were evaluated on NAFLD using an HFD-induced obese mouse model. Abstract : In this study, Bletilla striata polysaccharides were degraded into oligosaccharides. The structural features were analyzed by HPLC, HPLC-MS, FT-IR, and NMR spectroscopy. The results indicated that Bletilla striata oligosaccharides (BOs) were composed of mannose and glucose with a molar ratio of 5.2 : 1, and the main backbones of BOs contained (1→4)-linked-α-d -Man, (1→2)-linked-α-d -Man, and (1→2)-linked-α-d -Glc. By using a high-fat diet (HFD)-induced mouse model, we demonstrated that BOs had an improving effect on non-alcoholic fatty liver disease (NAFLD). Using the metabolomics assay, we found that BOs significantly regulated the hepatic metabolism of fatty acids, arachidonic acid, and other related metabolites in HFD-fed mice, accompanied by the reduction of lipid accumulation and fibrosis in liver tissues. In summary, BOs displayed high potential for the treatment of NAFLD as a functional food.